Study on the Basic Mechanical Properties of Waste Steel Fiber Reinforced Concrete After High-Temperature Exposure - Dan Yang; Xiaopeng Ren; Yongtao Gao; Tao Fan; Mingshuai Li; Hui Lv (Buildings)
The increasing incidence of urban fires poses significant threats to structural integrity, underscoring the urgent need for concrete materials with enhanced mechanical properties post-fire. Incorporating recycled waste steel fibers (WSF) from industrial byproducts into concrete not only bolsters its crack resistance but also advances circular economy principles by transforming industrial waste into valuable resources. Although a large amount of research has focused on native steel fiber-reinforced concrete, there is still a lack of systematic exploration on the optimal dosage and effectiveness of waste steel fibers in slowing down the strength degradation of concrete after high-temperature action. In this study, two grades of concrete (C40 and C60) containing 0%, 1%, and 2% WSF by volume were subjected to heating cycles ranging from 200 °C to 800 °C. Post-cooling evaluations encompassed mass loss quantification, cube compressive strength testing (using 100 mm3 specimens), and splitting tensile tests conducted at a loading rate of 0.1 MPa/s. Results indicated that mass loss escalated to 11% at 800 °C, with C60 experiencing a 12% higher loss compared to C40. Compressive strength decreased by 15% for every 200 °C increment; however, the inclusion of 1% WSF significantly minimized this degradation, preserving 44.5% (for C40) and 37.8% (for C60) of the original strength at 800 °C. Notably, the splitting tensile strength of 1% WSF-reinforced C60 concrete exceeded that of plain concrete by 39.4% after exposure to 800 °C, demonstrating its superior crack-bridging capabilities.